PERANAN MODAL SOSIAL PADA KELOMPOK TANI PADI SAWAH DI DESA TATENGESAN KECAMATAN PUSOMAEN KABUPATEN MIHAHASA TENGGARA - Antou, Jesica Iin; Jocom, Sherly Gladys; Moniaga, Vicky Richard Bernhard (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the role of social capital in lowland rice farmer groups in Tatengesan Village, Pusomaen District, Southeast Minahasa Regency. This research was carried out from September to October 2021. The data collected in this study were primary data obtained from direct interviews with members of lowland rice farmer groups using a questionnaire. Secondary data was obtained from the Tatengesan Village Office, as well as data related to research taken from the internet. Sampling was done by purposive sampling, which was as many as 20 samples. The results of the study showed the role of social capital in the lowland rice farmer group in Tatengesan Village that the role index had a total score of 1.197 with a percentage of 79.8% included in the role category.